(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India has the second-highest population in the world at 1.3 billion, or around 18 of the total. Asustainable method in the form of a digital payment system is required to address the financial servicedemands of a rising population. The use of digital payment systems is advantageous because of the manybenefits they provide, including convenience, simplicity of transactions, and safety. This research paperexamines the development of digital payments from 2012–2013 to 2018–2019 in terms of volume and valueof transactions. After seven years, the total volume and value of digital payments in the nation haveincreased, according to this survey. In addition, the value of digital transactions in the nation isprojected to surpass INR 15,20,000,000,000 in 2020-2021, or 28,000,000 transactions per year. Micro,small, and medium-sized businesses (MSMBs) are the driving force behind economic development inevery emerging nation. One drawback of electronic payment is that it may make it more difficult forcustomers to make purchases, especially if they have to add funds to their accounts before makingpurchases or if just one sort of electronic payment is accepted at a given counter. This researchconcludes that e-money is being redirected from its original purposepaymentto serve as a marketing toolfor small and medium-sized enterprises.